A heat-treatment-free high-strength and toughness die-casting aluminum alloy material and preparation method thereof

By introducing ZrNi alloy and other elements into aluminum alloys, combined with multi-stage filtration and refining agent spraying technology, the hydrogen embrittlement problem and the problem of low efficiency of traditional hydrogen removal processes are solved, and aluminum alloys with high strength and toughness and anti-hydrogen embrittlement properties are achieved. Materials ensure the full life cycle performance and production efficiency of aluminum alloys.

CN118685670BActive Publication Date: 2024-12-17SHANDONG HAIHUA GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411199921.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-17
Estimated Expiration
2044-08-29

AI Technical Summary

Technical Problem

Existing heat-free aluminum alloy materials are prone to hydrogen embrittlement problems in high temperature and high humidity environments, resulting in reduced strength and shortened fatigue life. In addition, traditional hydrogen removal processes have safety hazards and low efficiency, making it difficult to achieve effective control of the entire life cycle of aluminum alloys. .

Method used

Using ZrNi alloy and elements such as Si, Mg, Cr, Sr, etc., through multi-stage filtration and refining agent spraying technology, a die-cast aluminum alloy with matrix α-Al solid solution and ZrNi phase is constructed to achieve effective control of hydrogen and slag content. , ensure the high strength and toughness of aluminum alloy and the anti-hydrogen embrittlement properties.

Benefits of technology

The extremely low hydrogen and slag content of aluminum alloy is achieved, the yield strength, tensile strength and elongation are improved, the risk of hydrogen embrittlement is significantly reduced, and the full life cycle performance stability and production efficiency of aluminum alloy are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118685670B_ABST
    Figure CN118685670B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-strength and tough die-cast aluminum alloy material without heat treatment and a preparation method thereof, belonging to the technical field of aluminum alloy materials. The weight percentage of each component in the die-cast aluminum alloy is Si: 6.0-12%, Mg: 0.1-0.45%, Mn: 0.3-0.85%, Cr: 0.05-0.2%, Sr: 0.05-0.15%, Zr: 0.05-0.12%, Ni: 0.03-0.07%, Fe<0.2%, the total amount of other impurities is ≤0.5%, and the balance is Al. The die-cast aluminum alloy phase includes a matrix α-Al solid solution, Si and ZrNi phases; the ZrNi phase is uniformly distributed near the grain boundary of the die-cast aluminum alloy, and has a strength of 5×10 ‑4 Pa hydrogen absorption equilibrium pressure and hydrogen adsorption capacity exceeding 200ml / g, and no melting occurs when heated to 1010℃, the hydrogen content of aluminum liquid is ≤0.04ml / 100g Al, and the slag content is ≤0.008mm 2 / kg, the obtained heat-treatment-free die-casting aluminum alloy has excellent strength and toughness and high resistance to hydrogen embrittlement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloy materials, and in particular to a heat treatment-free high-strength and toughness die-casting aluminum alloy material and a preparation method thereof. Background Art

[0002] The development of high-strength and tough aluminum alloy die-castings for automotive body structural parts began in the 1990s. A typical example is the all-aluminum body frame of the Audi A8, which uses aluminum alloy die-castings in key joints of the body. Such body structural parts are usually collision safety parts, connected by rivets, and require die-castings to have good toughness while maintaining good strength. With the rapid development of new energy vehicles, automotive structural parts are rapidly developing in the direction of integrated, lightweight, and efficient design and manufacturing, such as one-piece die-casting body and one-piece die-casting subframe. As a widely used die-casting aluminum alloy for vacuum die-casting structural parts of the body, the heat treatment process of AlSi10MnMg alloy will cause deformation and surface blistering of die-casting parts. In particular, as die-casting parts continue to grow in size, the difficulty of subsequent shaping and the scrap rate will increase significantly. Therefore, heat-treatment-free die-casting aluminum alloy materials can be used directly in the cast state to avoid the above problems, and on the other hand, they can also reduce the cost of parts manufacturing. In recent years, its development and application have gradually become a research hotspot. The Chinese patent document with publication number CN117867333A discloses a high-strength and tough heat-treatment-free aluminum alloy for high-pressure casting and a preparation method thereof, wherein the components include 5.0-15.0% La, 1.5-4.5% Er, 0.5-2.5% Cu, 0.3-1.5% Mg, 0.2-1.5% Zn, 0.05-0.30% Ag, 0.1-0.4% Mn, 0.05-0.35% Ti, 0.05-0.35% Sc, 0.05-0.25% Zr, and 0.05-0.35% Y. A high-strength and tough heat-treatment-free aluminum alloy with high casting formability, high strength and plasticity is prepared by combining a variety of light and heavy rare earth elements. However, too many alloying elements increase the controllable difficulty of aluminum alloying, and adding too many rare earths brings about the problem of high raw material costs, making it difficult to achieve industrial promotion and application; the Chinese patent document with publication number CN117867333A discloses a high-strength and tough heat-treatment-free aluminum alloy for high-pressure casting, high strength and plasticity, and a high-strength and tough heat-treatment-free aluminum alloy. However, too many alloying elements increase the controllable difficulty of aluminum alloying, and adding too many rare earths brings about the problem of high raw material costs, making it difficult to achieve industrial promotion and application; the Chinese patent document with publication number CN117867333A discloses a high-strength and tough heat-treatment-free aluminum alloy for high-pressure casting, high strength and plasticity, and a high strength and toughness heat-treatment-free aluminum alloy with high casting formability, high strength and plasticity, The Chinese patent document 117802363 A discloses a high-strength and toughness die-cast aluminum alloy that does not require heat treatment and a preparation method thereof. The aluminum alloy is composed of the following components in mass percentage: 9.5-12.5% ​​Si, 0.3-0.6% Mg, 0.5-1.5% Cu, 0.2-0.5% Mn, 0.1-0.2% Ti, 0.01-0.05% Sr, 0.005-0.015% P, the Fe content does not exceed 0.25%, and the rest is Al and impurities. The invention improves the strength and plasticity of the die-cast aluminum alloy by refining coarse α-Al grains and Si phases, eliminating the harm of hydrogen and inclusions to strength and plasticity. However, the toxic chlorine used for dehydrogenation has a great safety hazard, and the traditional process method of bubble floating and refining agent impurity removal has the problem of limited purification of aluminum liquid. The minimum hydrogen content and slag content of the aluminum alloy liquid after treatment are only 0.079 ml / 100 g Al and 0.065 mm 2 / kg, there is still a large amount of hydrogen and inclusions in the aluminum liquid that have not been removed. Hydrogen is the only gas that can dissolve in large quantities in aluminum liquid. It is very harmful to the performance of aluminum and aluminum alloys. It is very easy to precipitate from the castings during the heat treatment process to form surface bubbles. The scrap rate caused by excessive hydrogen content accounts for about half of all aluminum casting scraps. Hydrogen not only causes macroscopic defects in aluminum, but also affects the organizational structure, and has an impact on a series of properties such as strength, fatigue, toughness, corrosion resistance, and anodizing. Although heat-free aluminum alloys avoid the deformation of die castings and the generation of surface bubbles caused by heat treatment, if the hydrogen content in heat-free aluminum alloys is too high, in addition to reducing the strength and toughness of aluminum alloy die castings, it will significantly reduce fatigue life, and cause hydrogen embrittlement under the induction of external environments such as alternating stress, impact loads, and rain and seawater. The hydrogen content required for hydrogen embrittlement in aluminum and aluminum alloys is only about 0.1ml / 100g Al, which is one to two orders of magnitude lower than the hydrogen content in steel and titanium alloys. Therefore, considering the entire life cycle of heat-free aluminum alloy die castings from melting and casting to loading and application to scrapping, the hydrogen content of the aluminum liquid must be controlled below 0.1ml / 100g Al from the aluminum alloy melting and casting stage to avoid extreme accidents such as brittle fracture caused by hydrogen embrittlement. In addition, considering the entire life cycle of the casting, under the induction of application scenarios such as high temperature and high humidity water vapor and alternating impact stress, the hydrogen in the external environment and the supersaturated hydrogen atoms retained in the solid aluminum will become "restless". Once the hydrogen atoms combine into hydrogen molecules, they will be accompanied by a sharp volume expansion, and the internal stress generated can reach 10 4 MPa, which is enough to "tear" the aluminum alloy from the inside. In summary, heat-treatment-free aluminum alloys actually put forward more stringent requirements on aluminum alloy materials and each link of processing and preparation. Only by effectively controlling the hydrogen content and inclusion content in aluminum alloys, and at the same time using recycled waste aluminum with complex composition and more impurities as raw materials to manufacture high-strength and tough heat-treatment-free aluminum alloy materials, can we truly reduce costs and increase efficiency for enterprises, and promote the benign and healthy development of the heat-treatment-free die-casting aluminum alloy industry for automotive structural parts. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a high-strength and toughness die-cast aluminum alloy material and a preparation method thereof that does not require heat treatment, starting from the entire life cycle of the die-cast aluminum alloy. The high-strength and toughness die-cast aluminum alloy that does not require heat treatment achieves effective control of hydrogen and slag content, has high yield strength, tensile strength and elongation, and exhibits excellent toughness. At the same time, the high-strength and toughness die-cast aluminum alloy that does not require heat treatment has a high resistance to hydrogen embrittlement.

[0004] To achieve the above purpose, the weight percentage of each component in the die-casting aluminum alloy is Si: 6.0-12%, Mg: 0.1-0.45%, Mn: 0.3-0.85%, Cr: 0.05-0.2%, Sr: 0.05-0.15%, Zr: 0.05-0.12%, Ni: 0.03-0.07%, Fe<0.2%, the total amount of other impurities is ≤0.5%, and the balance is Al.

[0005] The die-cast aluminum alloy phases include matrix α-Al solid solution, Si and ZrNi phases; the orthorhombic ZrNi phase is uniformly distributed in the grain boundary region of the die-cast aluminum alloy, and has a 5×10 -4 Pa and a hydrogen absorption equilibrium pressure exceeding 200 ml / g, and no melting occurs when heated to 1010°C; the die-cast aluminum alloy has a die-cast tensile strength of 280-350 MPa, a yield strength of 150-198 MPa, and an elongation of 9-16%.

[0006] The preparation method of the present invention comprises the following steps:

[0007] 1) Put aluminum ingot, silicon, aluminum-chromium and aluminum-manganese master alloy into a smelting furnace, heat it to 750-780°C, stir it evenly for 15-30 minutes after the aluminum ingot is completely melted; then wait until the aluminum liquid is cooled to 680-710°C, add magnesium ingot and Al-Sr master alloy, press them into the bottom of the molten liquid to completely melt and stir evenly;

[0008] 2) The aluminum liquid is heated to 710-730°C, and the refining agent is evenly sprayed into the aluminum liquid with nitrogen load and maintained for 10-15 minutes. After the spraying is completed, the aluminum liquid is allowed to stand for 20-30 minutes to allow the refining agent particles to fully react and float up before slag removal; the refining agent spraying speed is 0.6-1.0 kg / min, and the nitrogen pressure is 0.35-0.8 MPa;

[0009] 3) After the alloy composition test is qualified, transfer the aluminum liquid to the holding furnace, turn on the rotary degasser in the middle of the holding furnace, set the rotor rotation speed to 400-450r / min, argon pressure to 0.2-0.35MPa, argon flow rate to 10-15L / min, and degassing time to 10-15min; sprinkle a layer of slag remover on the surface of the degassed aluminum liquid for slag removal, let it stand for 10-20min, control the aluminum liquid temperature to 660-690℃, and after three-stage filtration, obtain a hydrogen content of ≤0.04ml / 100g Al and a slag content of ≤0.008mm 2 / kg of aluminum liquid; the aluminum liquid enters the preheated ingot mold through a distributor to produce a heat-treatment-free die-casting aluminum alloy ingot.

[0010] The refining agent in step 2) is composed of the following components in mass fraction: KCl: 30-50wt%; MgCl2: 30-55wt%; CaF2: 5-10 wt%; BaCl2: 5-10 wt%; ZrNi alloy: 3-6 wt%; the ZrNi alloy in the refining agent is a powder particle with a particle size of 0.5-1 μm obtained by repeatedly smelting three times in a magnetic suspension smelting furnace and then ball milling. The refining agent is prepared by mixing the components according to the corresponding percentage and loading them into a ball mill with a rotation speed of 100-600 r / min, mixing and grinding them into powder, and then passing through a 30-60 mesh sieve.

[0011] The slag remover in the step 3) is MgCl2 and KCl in a weight ratio of 1: 1 to 1.5; the three-stage filtration is to set a glass cloth gate at the outlet of the aluminum liquid in the insulation furnace for primary filtration, then flow through a foam ceramic filter with a thickness of 8 to 20 mm and a pore size of 20 to 80 for secondary filtration, and finally flow through an alumina gravel deep bed filter with a particle size of 2 to 10 mm for third stage filtration.

[0012] The present invention has the following beneficial effects:

[0013] Starting from the whole life cycle of die-cast aluminum alloys that do not require heat treatment, the present invention introduces ZrNi alloys with extremely low hydrogen absorption equilibrium pressure and large hydrogen absorption capacity into the field of die-cast aluminum alloys for the first time, constructs a die-cast aluminum alloy composed of a matrix α-Al solid solution, Si and ZrNi phases, and prepares a high-strength and tough die-cast aluminum alloy that does not require heat treatment and has extremely low hydrogen and slag contents; Si is the main alloying element of die-cast aluminum alloys, and Si in die-cast aluminum alloys can improve the casting fluidity of aluminum alloys, is non-sticky to the mold and is suitable for die casting, while Si and Mg can form Mg2Si strengthening phases to significantly enhance the strength of die-cast aluminum alloys, the higher the Si content, the better the fluidity of the die-cast aluminum alloy, and the higher the strength, but too high Si content will reduce the plasticity of the die-cast aluminum alloy; Mg is an important strengthening element of die-cast aluminum alloys, and Mg and Si can form Mg2Si strengthening phases to significantly enhance the strength of die-cast aluminum alloys, and the higher the Mg content, the higher the strength of the die-cast aluminum alloy However, if the Mg content is too high, the plasticity of the die-cast aluminum alloy will be reduced. In the actual production process, the atomic ratio of Mg / Si is about 1.73, which has good comprehensive mechanical properties; MnAl6 generated by the reaction of Mn element with matrix Al has the same potential as pure aluminum, which can effectively improve the corrosion resistance of aluminum alloy. At the same time, Mn, as a high-temperature strengthening phase, has the effect of increasing the recrystallization temperature and inhibiting the coarsening of recrystallized grains, and can achieve solid solution strengthening of the alloy. In addition, Mn can generate spherical A13 (Fe, Mn) with Fe element, which effectively eliminates the harmful effect of Fe on aluminum alloy. Therefore, the present invention uses recycled aluminum with a high impurity iron content as raw material to achieve waste aluminum regeneration and reduce costs; Cr element is a typical dispersed phase forming element, which inhibits the recrystallization and grain growth of the alloy. Trace element Cr is easy to form a dispersed phase with Fe, replacing other harmful Fe-containing phases, and reducing the splitting effect of insoluble Fe-containing phases on the matrix. Sr is the most effective Si phase modifier recognized by Al-Si alloys. At the same time, it also has a good refining and modifying effect on α-Al, which greatly improves the mechanical properties of the alloy. Zr, as a trace element with multiple effects such as refining aluminum alloy structure and improving thermal stability, has been widely used in aluminum alloys. ZrNi alloy has a 5×10 -4Pa hydrogen absorption equilibrium pressure and more than 200ml / g hydrogen adsorption capacity can quickly absorb hydrogen in the aluminum liquid and the external environment that invades the aluminum alloy casting into the alloy to solidify into "metallic hydrogen", and the ZrNi alloy does not melt when heated to 1010℃, and has high thermal stability, ensuring extremely low hydrogen content throughout the entire process of aluminum liquid solidification and the entire life cycle of die-casting aluminum alloy, avoiding the occurrence of hydrogen embrittlement; in addition, 0.5~1μm ZrNi alloy fine particles are evenly distributed in the grain boundary area, acting as an effective nucleation substrate, refining the grain structure, reducing the degree of segregation, and promoting the refinement and homogenization of eutectic Si and matrix α-Al solid solution phase; the three-stage filtration combined with glass fiber cloth gate + foam ceramic filter + deep bed filter and the low-temperature insulation static sedimentation with a total time of 30~50min can effectively reduce the slag content and the iron content introduced by recycled aluminum. The yield strength of the die-cast aluminum alloy of the present invention can reach up to 198MPa, the tensile strength can reach up to 350MPa, the elongation can reach up to 16%, the aluminum liquid hydrogen content is ≤0.04ml / 100g Al, and the slag content is ≤0.008mm 2 / kg.

[0014] The raw material mineral resource reserves used in the present invention are sufficient, the raw material cost is low, and the recycled waste aluminum with complex composition and more impurities can be used as the raw material to manufacture high-strength and toughness aluminum alloys that do not require heat treatment, thereby reducing manufacturing costs and improving production efficiency. It can reduce costs and increase efficiency for enterprises, and promote the benign and healthy development of the heat-treatment-free die-casting aluminum alloy industry for automotive structural parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 XRD patterns of ZrNi alloys used in Examples 1 to 3;

[0016] Figure 2 The XRD pattern of the die-cast aluminum alloy prepared in Example 3;

[0017] Figure 3 This is a metallographic structure image of the die-cast aluminum alloy obtained in Example 2, magnified 1000 times;

[0018] Figure 4 This is a 3000x scanning electron microscope secondary electron image of the die-cast aluminum alloy prepared in Example 2;

[0019] Figure 5The secondary electron image of the die-cast aluminum alloy obtained in Example 3 at 3000 times scanning electron microscope. (The sample was corroded by 4% nitric acid alcohol solution (volume fraction), and the metallographic sample was observed on a Leica DM IRM optical microscope (OM) and a JEOL JXA-8100 scanning electron microscope (SEM) equipped with an OXFORD7412 energy dispersive spectrometer (EDS); the phase composition analysis was performed on a D / MAX-RC X-ray diffractometer (XRD) using a Cu target; the plate-shaped tensile sample was subjected to a room temperature (293K) tensile test on a DNS200 universal material testing machine, with a tensile speed of 2 mm•min -1 . ) DETAILED DESCRIPTION

[0020] For a better understanding of the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments. However, the protection scope of the present invention is not limited to the description scope of the embodiments. Example 1

[0021] A heat-treatment-free high-strength and tough die-cast aluminum alloy material, the weight percentage of each component is Si: 12%, Mg: 0.1%, Mn: 0.3%, Cr: 0.05%, Sr: 0.15%, Zr: 0.05%, Ni: 0.03%, Fe: 0.12%, the total amount of other impurities is 0.5%, and the balance is Al. The die-cast aluminum alloy phase of this embodiment includes a matrix α-Al solid solution, Si and ZrNi phases, and the ZrNi alloy is obtained by repeatedly smelting three times in a magnetic suspension melting furnace and then ball milling and screening. Figure 1 As shown in the figure, the particle size is 0.5 μm. The orthorhombic ZrNi phase is evenly distributed in the grain boundary region of the die-cast aluminum alloy, with a particle size of 5×10 -4 Pa and a hydrogen absorption equilibrium pressure exceeding 200 ml / g, and no melting occurs when heated to 1010°C; the die-cast aluminum alloy in this embodiment has a die-cast tensile strength of 350 MPa, a yield strength of 198 MPa, and an elongation of 9%.

[0022] A method for preparing a heat-treatment-free high-strength and toughness die-cast aluminum alloy material comprises the following steps:

[0023] 1) Put the recycled aluminum ingot, silicon, aluminum-chromium and aluminum-manganese master alloy into the smelting furnace, heat it to 750°C, stir it evenly for 15 minutes after the aluminum ingot is completely melted; then wait until the aluminum liquid is cooled to 680°C, add the magnesium ingot and Al-Sr master alloy, press them into the bottom of the molten liquid to completely melt and stir them evenly;

[0024] 2) The aluminum liquid is heated to 710°C, and the refining agent is evenly sprayed into the aluminum liquid with nitrogen load and maintained for 10 minutes. After the spraying is completed, the aluminum liquid is allowed to stand for 20 minutes to allow the refining agent particles to fully react and float up before slag removal; the refining agent is sprayed at a speed of 0.6 kg / min and a nitrogen pressure of 0.35 MPa; the refining agent is prepared by mixing the components according to the corresponding percentages and loading them into a ball mill with a rotation speed of 100 r / min, mixing and grinding them into powder, and then passing through a 30-mesh sieve, and the percentages of the components constituting the refining agent are MgCl2: 42 wt%, KCl: 35 wt%, CaF2: 10 wt%, BaCl2: 10 wt%, and ZrNi alloy: 3 wt%;

[0025] 3) After the alloy composition test is qualified, the aluminum liquid is transferred to the holding furnace, and the rotary degasser in the middle of the holding furnace is turned on. The rotor rotation speed is set to 400r / min, the argon pressure is 0.2MPa, the argon flow rate is 10L / min, and the degassing time is 10min; a layer of slag remover composed of MgCl2 and KCl with a weight ratio of 1:1 is evenly sprinkled on the surface of the degassed aluminum liquid for slag removal. After standing for 10 minutes, the aluminum liquid temperature is controlled to 660℃, and a glass cloth gate is set at the outlet of the aluminum liquid in the holding furnace for primary filtration, and then it flows through a foam ceramic filter with a thickness of 8mm and an aperture of 20 mesh for secondary filtration, and finally flows through an alumina gravel deep bed filter with a particle size of 10mm for third-stage filtration. After three-stage filtration, a hydrogen content of 0.04ml / 100g Al and a slag content of 0.008mm 2 / kg of aluminum liquid; the aluminum liquid enters the preheated ingot mold through a distributor, and the resulting heat-treatment-free die-casting aluminum alloy has excellent strength and toughness and a high degree of resistance to hydrogen embrittlement. Example 2

[0026] A heat-treatment-free high-strength and tough die-cast aluminum alloy material, the weight percentage of each component is Si: 6.0%, Mg: 0.45%, Mn: 0.85%, Cr: 0.2%, Sr: 0.05%, Zr: 0.12%, Ni: 0.07%, Fe: 0.15%, the total amount of other impurities is 0.4%, and the balance is Al. The die-cast aluminum alloy phase of this embodiment includes a matrix α-Al solid solution, Si and ZrNi phases, such as Figure 3 Metallographic structure and Figure 4 As shown in the scanning electron microscope image; Figure 3 The metallographic structure clearly shows the α-Al solid solution grains with a grain size of about 10 μm and the eutectic silicon phase distributed between the α-Al solid solution grains. Figure 4 The scanning electron microscope image shows that the Al2O3 crystals with a grain size of about 10 μm are generated due to the high Mn content in this example. 4.01 MnSi 0.74 The ZrNi alloy is obtained by repeatedly melting three times in a magnetic suspension melting furnace and then ball milling and sieving. Figure 1 As shown in the figure, the particle size is 1.0 μm. The orthorhombic ZrNi phase is evenly distributed in the grain boundary region of the die-cast aluminum alloy, with a particle size of 5×10 -4 Pa and a hydrogen absorption equilibrium pressure exceeding 200 ml / g, and no melting occurs when heated to 1010°C; the die-cast aluminum alloy in this embodiment has a die-cast tensile strength of 280 MPa, a yield strength of 150 MPa, and an elongation of 16%.

[0027] A method for preparing a heat-treatment-free high-strength and toughness die-cast aluminum alloy material comprises the following steps:

[0028] 1) Put the recycled aluminum ingot, silicon, aluminum-chromium and aluminum-manganese master alloy into the melting furnace, heat it to 780°C, stir it evenly for 30 minutes after the aluminum ingot is completely melted; then wait until the aluminum liquid is cooled to 710°C, add the magnesium ingot and Al-Sr master alloy, press them into the bottom of the melt to completely melt and stir them evenly;

[0029] 2) The aluminum liquid is heated to 730°C, and the refining agent is evenly sprayed into the aluminum liquid with nitrogen load and maintained for 15 minutes. After the spraying is completed, the aluminum liquid is allowed to stand for 30 minutes to allow the refining agent particles to fully react and float up before slag removal; the refining agent is sprayed at a speed of 1.0 kg / min and a nitrogen pressure of 0.8 MPa; the refining agent is prepared by mixing the components according to corresponding percentages and loading them into a ball mill with a rotation speed of 600 r / min, mixing and grinding them into powder, and then passing through a 60-mesh sieve, and the percentages of the components constituting the refining agent are MgCl2: 34 wt%, KCl: 50 wt%, CaF2: 5 wt%, BaCl2: 5 wt%, and ZrNi alloy: 6 wt%;

[0030] 3) After the alloy composition test is qualified, the aluminum liquid is transferred to the holding furnace, and the rotary degasser in the middle of the holding furnace is turned on. The rotor rotation speed is set to 450r / min, the argon pressure is 0.35MPa, the argon flow rate is 15L / min, and the degassing time is 15min. A layer of slag remover composed of MgCl2 and KCl with a weight ratio of 1: 1.5 is evenly sprinkled on the surface of the degassed aluminum liquid for slag removal. After standing for 20 minutes, the aluminum liquid temperature is controlled to 690℃, and a glass cloth gate is set at the outlet of the aluminum liquid in the holding furnace for primary filtration. Then it flows through a foam ceramic filter with a thickness of 20mm and an aperture of 80 mesh for secondary filtration, and finally flows through an alumina gravel deep bed filter with a particle size of 2mm for third-stage filtration. After three-stage filtration, a hydrogen content of 0.01ml / 100g Al and a slag content of 0.004mm 2 / kg of aluminum liquid; the aluminum liquid enters the preheated ingot mold through a distributor, and the resulting heat-treatment-free die-casting aluminum alloy has excellent strength and toughness and a high degree of resistance to hydrogen embrittlement. Example 3

[0031] A heat-treatment-free high-strength and tough die-cast aluminum alloy material, the weight percentage of each component is Si: 9%, Mg: 0.2%, Mn: 0.5%, Cr: 0.15%, Sr: 0.1%, Zr: 0.09%, Ni: 0.05%, Fe: 0.1%, the total amount of other impurities is 0.3%, and the balance is Al. The die-cast aluminum alloy phase of this embodiment includes a matrix α-Al solid solution, Si and ZrNi phases, such as Figure 2 As shown in FIG. 1 , the ZrNi alloy is obtained by repeatedly melting three times in a magnetic suspension melting furnace and then ball milling and sieving. Figure 1 As shown in the figure, the particle size is 0.75 μm. The orthorhombic ZrNi phase is evenly distributed in the grain boundary region of the die-cast aluminum alloy, with a particle size of 5×10 -4 Pa hydrogen absorption equilibrium pressure and hydrogen adsorption capacity of more than 200ml / g, and it does not melt when heated to 1010℃; due to the low content of ZrNi phase, no corresponding diffraction peak appears in the XRD spectrum, but Figure 5 From the scanning electron microscope image magnified 3000 times, it can be clearly observed that ZrNi phase particles with a particle size of about 0.75 μm are evenly distributed in the eutectic Si phase region of the die-cast aluminum alloy. The eutectic Si grains are significantly refined under the action of the ZrNi alloy particle refiner. The granular eutectic Si grain size is about 1 μm, and some eutectic Si grains exist in the form of short rods. The die-cast tensile strength of the die-cast aluminum alloy in this embodiment is 310 MPa, the yield strength is 174 MPa, and the elongation is 11.5%.

[0032] A method for preparing a heat-treatment-free high-strength and toughness die-cast aluminum alloy material comprises the following steps:

[0033] 1) Put the recycled aluminum ingot, silicon, aluminum-chromium and aluminum-manganese master alloy into the melting furnace, heat it to 760°C, stir it evenly for 25 minutes after the aluminum ingot is completely melted; then wait until the aluminum liquid is cooled to 700°C, add the magnesium ingot and Al-Sr master alloy, press them into the bottom of the melt to completely melt and stir them evenly;

[0034] 2) Raise the temperature of the aluminum liquid to 720°C, spray the refining agent evenly into the aluminum liquid with nitrogen load and keep it for 13 minutes. After the spraying is completed, let the aluminum liquid stand for 25 minutes to allow the refining agent particles to fully react and float up before removing the slag; the spraying speed of the refining agent is 0.8kg / min, and the nitrogen pressure is 0.6MPa; the refining agent is composed of the following components in mass fraction. The refining agent is prepared by mixing the components according to the corresponding percentage and loading them into a ball mill with a rotation speed of 400r / min, mixing and grinding them into powder, and then passing through a 50-mesh sieve. The percentages of the components that make up the refining agent are MgCl2: 55wt%, KCl: 30wt%, CaF2: 5.5wt%, BaCl2: 5.5wt%, and ZrNi alloy: 4.5wt%;

[0035] 3) After the alloy composition test is qualified, the aluminum liquid is transferred to the holding furnace, and the rotary degasser in the middle of the holding furnace is turned on. The rotor rotation speed is set to 425r / min, the argon pressure is 0.3MPa, the argon flow rate is 13L / min, and the degassing time is 12min; a layer of slag remover composed of MgCl2 and KCl with a weight ratio of 1: 1.25 is evenly sprinkled on the surface of the degassed aluminum liquid for slag removal. After standing for 15 minutes, the aluminum liquid temperature is controlled to 675℃, and a glass cloth gate is set at the outlet of the aluminum liquid in the holding furnace for primary filtration, and then it flows through a foam ceramic filter with a thickness of 14mm and an aperture of 60 mesh for secondary filtration, and finally flows through an alumina gravel deep bed filter with a particle size of 6mm for third-stage filtration. After three-stage filtration, a hydrogen content of 0.02ml / 100g Al and a slag content of 0.006mm 2 / kg of aluminum liquid; the aluminum liquid enters the preheated ingot mold through a distributor, and the resulting heat-treatment-free integrated die-casting aluminum alloy ingot has excellent strength and toughness and a high degree of resistance to hydrogen embrittlement. Comparative Example

[0036] A recycled die-cast aluminum alloy, the weight percentage of each component is Si: 6.0%, Mg: 0.45%, Mn: 0.85%, Cr: 0.2%, Sr: 0.05%, Fe: 0.15%, the total amount of other impurities is 0.4%, and the balance is Al. The die-cast aluminum alloy phase of this embodiment includes a matrix α-Al solid solution and a Mg2Si phase; the die-cast aluminum alloy of this comparative example has a die-cast tensile strength of 275MPa, a yield strength of 132MPa, and an elongation of 5.74%.

[0037] A method for preparing a recycled die-cast aluminum alloy comprises the following steps:

[0038] 1) Put the recycled aluminum ingot, silicon, aluminum-chromium and aluminum-manganese master alloy into the melting furnace, heat it to 780°C, stir it evenly for 30 minutes after the aluminum ingot is completely melted; then wait until the aluminum liquid is cooled to 710°C, add the magnesium ingot and Al-Sr master alloy, press them into the bottom of the melt to completely melt and stir them evenly;

[0039] 2) The aluminum liquid is heated to 730°C, and the refining agent is evenly sprayed into the aluminum liquid with nitrogen load and maintained for 15 minutes. After the spraying is completed, the aluminum liquid is allowed to stand for 30 minutes to allow the refining agent particles to fully react and float up before slag removal; the refining agent is sprayed at a speed of 1.0 kg / min and a nitrogen pressure of 0.8 MPa; the refining agent is prepared by mixing the components according to the corresponding percentages and loading them into a ball mill with a rotation speed of 600 r / min, and then grinding them into powder and passing through a 60-mesh sieve, and the percentages of the components constituting the refining agent are MgCl2: 40wt%, KCl: 50wt%, CaF2: 5wt%, and BaCl2: 5wt%;

[0040] 3) After the alloy composition test is qualified, the aluminum liquid is transferred to the holding furnace, and the rotary degasser in the middle of the holding furnace is turned on. The rotor rotation speed is set to 450r / min, the argon pressure is 0.35MPa, the argon flow rate is 15L / min, and the degassing time is 15min; a layer of slag remover composed of MgCl2 and KCl with a weight ratio of 1: 1.5 is evenly sprinkled on the surface of the degassed aluminum liquid for slag removal. After standing for 20 minutes, the aluminum liquid temperature is controlled to 690℃, and a glass cloth gate is set at the outlet of the aluminum liquid in the holding furnace for primary filtration, and then it flows through a foam ceramic filter with a thickness of 20mm and an aperture of 80 mesh for secondary filtration, and finally flows through an alumina gravel deep bed filter with a particle size of 2mm for third-stage filtration. After three-stage filtration, a hydrogen content of 0.18ml / 100g Al and a slag content of 0.012mm 2 / kg of aluminum liquid; the aluminum liquid enters the preheated ingot mold through a distributor to produce a die-cast aluminum alloy ingot.

[0041]

[0042] It can be seen that compared with the embodiment, since ZrNi alloy is not added to the comparative refining agent, the diffusion rate of hydrogen in the aluminum liquid is reduced, and even after bubble floating and refining treatment with traditional refining agents, efficient dehydrogenation and degassing cannot be achieved, and the high hydrogen content in the aluminum liquid leads to a significant increase in the slag content, resulting in a significant decrease in the toughness of the obtained die-cast aluminum alloy. The hydrogen content and slag content in the aluminum liquid are directly related, and the hydrogen reduction and slag removal measures are mutually integrated and inseparable, as shown in the performance index comparison in Table 1 above.

Claims

1. A high-strength and tough die-cast aluminum alloy material without heat treatment, characterized in that: The weight percentage of each component in the die-casting aluminum alloy is Si: 6.0-12%, Mg: 0.1-0.45%, Mn: 0.3-0.85%, Cr: 0.05-0.2%, Sr: 0.05-0.15%, Zr: 0.05-0.12%, Ni: 0.03-0.07%, Fe<0.2%, the total amount of other impurities is ≤0.5%, and the balance is Al; The die-cast aluminum alloy phases include a matrix α-Al solid solution, Si and ZrNi phases; the ZrNi phase belongs to the orthorhombic system and is uniformly distributed in the vicinity of the grain boundary of the die-cast aluminum alloy. -4 Pa and a hydrogen absorption equilibrium pressure exceeding 200 ml / g, and no melting occurs when heated to 1010°C; the die-cast aluminum alloy has a die-cast tensile strength of 280-350 MPa, a yield strength of 150-198 MPa, and an elongation of 9-16%.

2. A method for preparing a heat-treatment-free high-strength and toughness die-cast aluminum alloy material as claimed in claim 1, characterized in that The following steps are involved: 1) Put the recycled aluminum ingot, silicon, aluminum-chromium and aluminum-manganese master alloy into the melting furnace, raise the temperature to 750-780°C, stir evenly for 15-30 minutes after the aluminum ingot is completely melted; then wait until the aluminum liquid is cooled to 680-710°C, add the magnesium ingot and Al-Sr master alloy, press them into the bottom of the melt to completely melt and stir evenly; 2) The aluminum liquid is heated to 710-730°C, and the refining agent is evenly sprayed into the aluminum liquid with nitrogen load and maintained for 10-15 minutes. After the spraying is completed, the aluminum liquid is allowed to stand for 20-30 minutes to allow the refining agent particles to fully react and float before slag removal; the refining agent has a spraying speed of 0.6-1.0 kg / min and a nitrogen pressure of 0.35-0.8 MPa; the refining agent is composed of the following components in mass fractions: KCl: 30-50 wt%; MgCl2: 30-55 wt%; CaF2: 5-10 wt%; BaCl2: 5-10 wt%; ZrNi alloy: 3-6 wt%; 3) After the alloy composition test is qualified, transfer the aluminum liquid to the holding furnace, turn on the rotary degasser in the middle of the holding furnace, set the rotor rotation speed to 400-450r / min, argon pressure to 0.2-0.35MPa, argon flow rate to 10-15L / min, and degassing time to 10-15min; sprinkle a layer of slag remover on the surface of the degassed aluminum liquid for slag removal, let it stand for 10-20min, control the aluminum liquid temperature to 660-690℃, and after three-stage filtration, obtain a hydrogen content of ≤0.04ml / 100g Al and a slag content of ≤0.008mm 2 / kg of aluminum liquid; the aluminum liquid enters the preheated ingot mold through a distributor to produce a heat-treatment-free die-casting aluminum alloy ingot.

3. The method for preparing a heat treatment-free high-strength and toughness die-cast aluminum alloy material according to claim 2, characterized in that: The slag remover in step 3) is MgCl2 and KCl in a weight ratio of 1: 1 to 1.5; the three-stage filtration is to set a glass cloth gate at the outlet of the aluminum liquid in the insulation furnace for primary filtration, then flow through a foam ceramic filter with a thickness of 8 to 20 mm and an aperture of 20 to 80 meshes for secondary filtration, and finally flow through an alumina gravel deep bed filter with a particle size of 2 to 10 mm for third-stage filtration.

4. The method for preparing a heat-treatment-free high-strength and toughness die-casting aluminum alloy material according to claim 2, characterized in that: The refining agent is prepared by mixing the components according to corresponding percentages and feeding them into a ball mill with a rotation speed of 100-600 r / min, mixing and grinding them into powder, and then passing through a 30-60 mesh sieve.

5. The method for preparing a heat-treatment-free high-strength and toughness die-casting aluminum alloy material according to claim 2, characterized in that: The ZrNi alloy is a powder particle with a particle size of 0.5-1 μm obtained by repeatedly smelting three times in a magnetic suspension smelting furnace and then ball milling and sieving.